CONSTRUCTION OF PENALIZATION IN PERSONAL DATA PROTECTION FOR UTILIZATION OF FINANCIAL TECHNOLOGY APPLICATIONS - Erwin Asmadi (Proceeding International Seminar of Islamic Studies, 2023)
Advances in technology and information are also increasingly eroding the boundaries of privacy belonging to others. It is very easy for someone's personal data to be shared and misused. Vigilance of this crime must always be put forward. because the purpose of this hack is usually to carry out fraud mode, data tapping, hacking, email spamming, and also manipulation of other people's data, which will then result in both material and immaterial losses. The research method used is normative juridical research, namely legal research conducted by examining literature or secondary data. Bank Indonesia Regulation Number 19/12/PBI/2017 concerning the Implementation of Financial Technology, explained that one of these regulations was made by considering the needs of the community related to innovation in the field of financial technology services. For the sake of improving and developing this financial technology, it has been regulated in Bank Indonesia regulation Number 19/12/17, specifically in Article 11 paragraph (1) that every financial technology operator must first be tested through a Regulatory Sandbox organized by Bank Indonesia. The existence of a Regulatory Sandbox aims to prevent various risks that exist in Fintech innovation when products are marketed, such as: customer confidentiality, data theft, cyber attacks and various other risks.